Paternal Depression Screening Practices of Healthcare Providers - Estrada, Mary Kathleene (The University of Arizona., 2015)
Background: Becoming a parent can elicit many emotions. For some parents, it can be a time of anxiety and depression. Fathers are not exempt from this type of depression. Paternal depression (PD) is a serious health issue with long lasting consequences for both the father and child. Unfortunately, little research has been done on PD. The research that has been done recommends routine PD screening. Methods: A cross-sectional descriptive study design was used to determine the current PD screening practices and screening tools of providers in the Tucson area. The study sample consisted of randomly selected healthcare providers. The total number of possible participants was eighty two. Participants were provided a 20 question survey to assess screening practices as well as the beliefs, attitudes, norms, and confidence of providers regarding PD screening. Results: The study found many providers routinely screen for maternal depression but few screen for PD. While providers did recognize the impact PD has on children, this belief was not enough to implement screening. Most providers were unsure if PD was serious or if PD screening and therapy were effective. Few providers had any training or education regarding PD and few were confident in their ability to screen for PD. Providers who felt confident in their ability to screen, acknowledge the USPTF recommendation for screening all adults for depression, and had positive beliefs/attitudes regarding PD screening were more likely to have incorporated screening into practice. Of those who do screen, the majority do not use a validated screening. Conclusions: Although research recommends PD screening, it has not been implemented into practice. Training and education regarding PD is also lacking. The next step in research is to implement interventions that improve screening practices among providers, increase provider confidence in screening, and increase provider's awareness about PD.